2020
DOI: 10.1186/s12909-020-02161-x
|View full text |Cite
|
Sign up to set email alerts
|

Addressing knowledge gaps in Parkinson’s disease: a report on the Movement Disorder Society’s Centre-to-Centre initiative to improve Parkinson’s disease services in Lao People’s Democratic Republic

Abstract: Background: Lao People's Democratic Republic (Lao PDR) has only nine neurologists for seven million people; none have formal training in Parkinson's disease (PD). Medical specialists require sufficient PD knowledge to provide high-quality care. Methods: This study outlines a Centre-to-Centre programme for developing PD expertise in underserved regions through a tailored two-year educational enterprise between an established movement disorder mentor centre at Chulalongkorn University in Thailand and mentee cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A research conducted in Lao (The Lao People's Democratic Republic) found that the greatest lack of knowledge among doctors is in relation to non-motor symptoms and the impact of drugs on PD (Phokaewvarangkul, et al, 2020). In Thailand, a group of researchers detected gaps in the knowledge of neurologists, residents, intensivists, general practitioners and nurses about diagnosis, pharmacological options, and progression of PD, thus, the authors suggested didactic training, conference presentations, journal articles, meetings and small group discussions to promote the professionals' reflection on the phenomenon so that this knowledge gap is filled (Bhidayasiri, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A research conducted in Lao (The Lao People's Democratic Republic) found that the greatest lack of knowledge among doctors is in relation to non-motor symptoms and the impact of drugs on PD (Phokaewvarangkul, et al, 2020). In Thailand, a group of researchers detected gaps in the knowledge of neurologists, residents, intensivists, general practitioners and nurses about diagnosis, pharmacological options, and progression of PD, thus, the authors suggested didactic training, conference presentations, journal articles, meetings and small group discussions to promote the professionals' reflection on the phenomenon so that this knowledge gap is filled (Bhidayasiri, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the number of studies addressing the knowledge of health professionals correlating with PD (Cohen, et al, 2016, Phokaewvarangkul, et al, 2020Bhidayasiri, et al, 2014;Skelly, et al, 2015;Van Rumund, et al, 2014), a lack of research on the knowledge of SUDPAR among them is observed, reflecting the urgent need to use educational strategies so that the concept of SUDPAR is recognized among health professionals in order to prevent the tragic outcome in PD patients.…”
Section: Discussionmentioning
confidence: 99%